2007
DOI: 10.1016/j.chembiol.2007.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Structural Engineering of pMHC Reagents for T Cell Vaccines and Diagnostics

Abstract: MHC class I peptide complexes (pMHC) are routinely used to enumerate T cell populations and are currently being evaluated as vaccines to tumors and specific pathogens. Herein, we describe the structures of three generations of single-chain pMHC progressively designed for the optimal presentation of covalently associated epitopes. Our ultimate design employs a versatile disulfide trap between an invariant MHC residue and a short C-terminal peptide extension. This general strategy is nondisruptive of native pMHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 59 publications
4
75
1
Order By: Relevance
“…The SCT-K b construct was modified to produce a more stable SCT-K b in which the SIINFEKL peptide sequence was covalently linked to the α1 helix of K b (25,26). Tetramers of this SCT-K b molecule bound specifically to Ly49C + NK cells.…”
Section: Resultsmentioning
confidence: 99%
“…The SCT-K b construct was modified to produce a more stable SCT-K b in which the SIINFEKL peptide sequence was covalently linked to the α1 helix of K b (25,26). Tetramers of this SCT-K b molecule bound specifically to Ly49C + NK cells.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, we have successfully incorporated a disulfide trap into recombinant K b /OVA without SCT linkers by introducing cysteines into the recombinant heavy chain protein and synthetic peptide. These disulfide trap MHC-I tetramers stained T cells specific for K b /OVA as well as NK cells expressing the cognate Ly49 NK inhibitory receptor (24). Thus the disulfide trap preserves MHC-I antigen specificity and is a promising option where the loss of peptide is a critical limitation.…”
Section: Discussionmentioning
confidence: 99%
“…The clear implication of these findings was that the superior surface stability of the SCT compared with native K b /OVA was not due to continuous peptide binding, but rather the ability to rebind the linker-attached peptide. Subsequent crystallographic studies of the K b /OVA SCT demonstrated that the linker extending from the OVA peptide moiety disrupted a highly conserved H-bonding network that normally serves to anchor peptide at the C terminus (24). Specifically, the heavy chain residue Tyr-84 forced the linker to protrude above from the peptide binding platform, thereby disrupting the H-bonding network of the peptide C terminus with the heavy chain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, SCTs allow peptides with very weak affinity for MHC to be anchored into the peptide binding groove through a disulfide bond between the linker and heavy chain ( Fig. 2A) (7)(8)(9). Moreover, SCTs are recognized as intact molecules, because the D227K mutation in the α3 domain of the OVA/K b SCT abrogates CD8 interaction (14) and induces diminished K b -specific CD8 + T-cell responses when used in a DNA vaccine (Fig.…”
Section: Resultsmentioning
confidence: 99%